2022
DOI: 10.3390/genes13112110
|View full text |Cite|
|
Sign up to set email alerts
|

PCR-Based Screening of Spinal Muscular Atrophy for Newborn Infants in Hyogo Prefecture, Japan

Abstract: Spinal muscular atrophy (SMA) is a common devastating neuromuscular disorder, usually involving homozygous deletion of the SMN1 gene. Newly developed drugs can improve the motor functions of infants with SMA when treated in the early stage. To ensure early diagnosis, newborn screening for SMA (SMA-NBS) via PCR-based genetic testing with dried blood spots (DBSs) has been spreading throughout Japan. In Hyogo Prefecture, we performed a pilot study of SMA-NBS to assess newborn infants who underwent routine newborn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 47 publications
0
26
1
Order By: Relevance
“…Neonatal screening for SMA has already been reported in many other countries, such as Australia, Germany, Belgium, Canada, United States, Italy, Japan, and Taiwan ( Chien et al, 2017 ; Kariyawasam et al, 2020 ; Boemer et al, 2021 ; Vill et al, 2021 ; Abiusi et al, 2022 ; Kernohan et al, 2022 ; Lee et al, 2022 ; Matteson et al, 2022 ; Noguchi et al, 2022 ). Among the methodologies employed in the studies, real-time qPCR was the most used for initial screening.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Neonatal screening for SMA has already been reported in many other countries, such as Australia, Germany, Belgium, Canada, United States, Italy, Japan, and Taiwan ( Chien et al, 2017 ; Kariyawasam et al, 2020 ; Boemer et al, 2021 ; Vill et al, 2021 ; Abiusi et al, 2022 ; Kernohan et al, 2022 ; Lee et al, 2022 ; Matteson et al, 2022 ; Noguchi et al, 2022 ). Among the methodologies employed in the studies, real-time qPCR was the most used for initial screening.…”
Section: Discussionmentioning
confidence: 97%
“…The study done in Australia reported 10 positive cases after initial screening by real-time qPCR using a commercial kit, with only one case determined as false-positive after analysis by ddPCR (Kariyawasam et al , 2020). In the study carried out in Japan, 12 positive cases were reported after screening by real-time qPCR using a commercial kit, and 10 cases were determined to be false-positives after confirmatory analysis by MLPA ( Noguchi et al , 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main manifestation is progressive muscle weakness mainly in the proximal extremities, and as the disease progresses, multi-system involvement such as respiratory, digestive, and skeletal systems may occur. Fortunately, there were many ways to screen for SMA to prevent the birth of a child with SMA ( 23 25 ). If both spouses are SMA carriers, their offspring have a 25% probability of having SMA or the normal genotype, and a 50% probability of being carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Differential diagnosis for hypotonia is difficult, particularly in the neonatal period. Development of respiratory or other problems in an infant with hypotonia can hamper the suspicion of SMA [163]. In such cases, SMA cannot be diagnosed without newborn screening, and its diagnosis will be delayed by several weeks or months because of the time needed for clinical referrals and investigations.…”
Section: Prevention Of Delayed Diagnosis Of Smamentioning
confidence: 99%